Future Libraries: Romance of LIS with Futurology - Sridhar, M. S. (Journal of Information and Knowledge, 2019)
The paper examines the past ‘romance’ of LIS with futurology, traces the flaws of disintermediation threat and the resultant repositioning options of LIS, stressing the need for imagination coupled with reason to turn experience into foresight; identifies the importance of physical space, content, and ambience of libraries to move from ‘Transactional library’ to ‘Relational library’ and from a ‘Center of information’ to a ‘Center of culture’, enumerates a number of non-ICT innovations that have already taken place in libraries, mentions technologies that can be considered for their appropriateness and adoption to enhance value of services. In conclusion, highlights how libraries are marginalized in the digital era by putting ‘access’ before ‘selection’ (avoiding filtering at the input stage) and giving away control over organization of information to users, how ‘access to excess’ and speed over-ride the validity and the quality of content leading to distracted and dissatisfied users; finally cautions about equating ‘provision for access’ to utility and need for greater understanding of user-behaviour in the digital domain.